The Roles of Morphology and Environment on the Star Formation Rate–Stellar Mass Relation in COSMOS from 0 < z < 3.5 - Kevin C. Cooke; Jeyhan S. Kartaltepe; Caitlin Rose; K. D. Tyler; Behnam Darvish; Sarah K. Leslie; Ying-jie Peng; Boris Häußler; Anton M. Koekemoer (The Astrophysical Journal, 2023)
We investigate the relationship between environment, morphology, and the star formation rate (SFR)–stellar mass relation derived from a sample of star-forming (SF) galaxies (commonly referred to as the “star formation main sequence”, SFMS) in the COSMOS field from 0 < z < 3.5. We constructed and fit the far-UV–far-IR spectral energy distributions of our stellar-mass-selected sample of 111,537 galaxies with stellar and dust emission models using the public packages MAGPHYS and SED3FIT . From the best-fit parameter estimates, we construct the SFR–stellar mass relation as a function of redshift, local environment, NUVrJ color diagnostics, and morphology. We find that the shape of the main sequence derived from our color–color and specific-star-formation-rate-selected SF galaxy population, including the turnover at high stellar mass, does not exhibit an environmental dependence at any redshift from 0 < z < 3.5. We investigate the role of morphology in the high-mass end of the SFMS to determine whether bulge growth is driving the high-mass turnover. We find that SF galaxies experience this turnover independent of bulge-to-total ratio, strengthening the case that the turnover is due to the disk component’s specific SFR evolving with stellar mass rather than bulge growth.